(Anti-)deuteron production in pp collisions at √s=13TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Köhler, Markus Konrad; Leardini, Lucia; Martin, Nicole Alice; Ohlson, Alice; et al. (The European physical journal. C, Particles and fields, 2020)
The study of (anti-)deuteron production in pp collisions has proven to be a powerful tool to investigate the formation mechanism of loosely bound states in high-energy hadronic collisions. In this paper the production of $$\text {(anti-)deuterons}$$(anti-)deuteronsis studied as a function of the charged particle multiplicity in inelastic pp collisions at $$\sqrt{s}=13$$s=13TeV using the ALICE experiment. Thanks to the large number of accumulated minimum bias events, it has been possible to measure (anti-)deuteron production in pp collisions up to the same charged particle multiplicity ($${\mathrm {d} N_{ch}/\mathrm {d} \eta } \sim 26$$dNch/dη∼26) as measured in p-Pb collisions at similar centre-of-mass energies. Within the uncertainties, the deuteron yield in pp collisions resembles the one in p-Pb interactions, suggesting a common formation mechanism behind the production of light nuclei in hadronic interactions. In this context the measurements are compared with the expectations of coalescence and statistical hadronisation models (SHM).
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 18.11.2020